1998
DOI: 10.1007/s005200050175
|View full text |Cite
|
Sign up to set email alerts
|

The use of unproven methods of treatment by cancer patients

Abstract: The use of unproven therapies is of concern for a number of reasons, including the lack of scientific evidence of support them, their potential financial costs and the possibility of interference with conventional treatment. This study explored the prevalence, predictors and experiences of unproven therapy use by cancer patients attending an oncology clinic at an Australian teaching hospital. A questionnaire was administered to patients whilst they were waiting for a consultation with their oncologist. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 11 publications
3
85
1
Order By: Relevance
“…In a national US study involving 2527 breast cancer survivors, Saxe et al 4 reported that 80% used some form of CAM, and of these, 28% used CAM for cancerrelated reasons. Although there is a lack of scientifically credible research to support CAM influencing survival time, adoption of CAM may aid active coping during and following the treatment process, 5,6 assist in minimizing adverse side effects of conventional treatment, 4,6,7 and/or more closely reflect patient values and life philosophies, compared with allopathic medicine. 8 Given the high prevalence of CAM use as an adjunct to standard care among cancer patients and the potential for harmful interactions between certain types of CAM and conventional medicines, 9 it is important that clinicians and patients engage in an open dialogue about CAM use to ensure safe and integrated health care practices.…”
Section: Introductionmentioning
confidence: 99%
“…In a national US study involving 2527 breast cancer survivors, Saxe et al 4 reported that 80% used some form of CAM, and of these, 28% used CAM for cancerrelated reasons. Although there is a lack of scientifically credible research to support CAM influencing survival time, adoption of CAM may aid active coping during and following the treatment process, 5,6 assist in minimizing adverse side effects of conventional treatment, 4,6,7 and/or more closely reflect patient values and life philosophies, compared with allopathic medicine. 8 Given the high prevalence of CAM use as an adjunct to standard care among cancer patients and the potential for harmful interactions between certain types of CAM and conventional medicines, 9 it is important that clinicians and patients engage in an open dialogue about CAM use to ensure safe and integrated health care practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of profi le of patients who used CAM, studies showed that they are adults aged between 30 and 59 years of age, 5,7,12,14,19,26,28,29,30,38,43 female, 11,20,26,27,30,41,43 with a high level of education 3,6,9,14,17,19,20,28,29 and high family income, 7,14,19,26,28,29,41 with advanced-staged cancer, 6,7,23,26,30,37,39,42 belonging to some religious group 20 and ethnically infl uenced 1,17,19,37 in relation to the alternative therapy adopted.…”
Section: Discussionmentioning
confidence: 99%
“…1,9,24,40,45 In relation to the psychological motivation, the promotion of well-being, control of stress and improvement of life quality were described. 2,5,6,9,14,23,27,46 The technical reasons for the use of CAM in the treatment of cancer are intimately connected to the dissatisfaction with conventional treatment, 1,8,12,36,37 especially concerning side effects and the interaction that is formed with health professionals, 33 besides the autonomous, humanizing process promoted by non-conventional practices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In Australia, the use of CAM in cancer patients ranges from 17-65%. [4][5][6] The increasing trend in cancer patient use mirrors those of the general population and a recent study estimated 79% of cancer survivors had used at least one form of CAM in the last 12 months. 7 Additionally, 21% of non-English speaking Chinese Americans reported using CAM, particularly Chinese herbal medicine, acupuncture and Chinese massage for treating cancer related pain.…”
Section: Introductionmentioning
confidence: 99%